DIFFERENT APPROACHES TO THE FORMATION OF AMERICAN ENGLISH - Putayeva, E.E (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
This article outlines some considerations for historical research on American English (AE) from the seventeenth through the nineteenth century, a period of great changes, a time of multilateral contact with other languages and between varieties of English. In recent decades researchers have shown that quantitative variation within synchronic data sets often indicates ongoing change, even when that change does not proceed to completion, and in this regard, variation in AE over the past three to four generations is still actual. This article also explores the history and origins of American English, with a relevant focus on its linguistic diversity. English speaking community migrating to the Newland and the Caribbean beginning from the seventeenth century on had close contacts with Native American languages, and observed influences from Native American languages on American English vocabulary. They include words like gorilla, canoe, chimpanzee, chocolate and others, which have survived to the present day, and words like mangummenauk (an acorn which is edible) and netop (a reliable friend), which have not survived. This article surveys the linguistic development of American English, repeatedly acknowledging the inputs from its various ethnic variants: for example, bogus (African), juke-box (African American), cookie (Dutch), bayou (French), macaroni (Italian), geisha (Japanese), vigilante (Spanish), lutefish (Swedish), and bagel (Yiddish). Therefore, American English is more than the totality of inheritances from its "neighbor" languages. In the seventeenth century, for example, pidgin-like varieties of English were simple examples among both Amerindian and African speakers, and there was open respect for linguistic diversity and substantial interest in it.